Experimental investigation of monolithic tempered glass fragment characteristics subjected to blast loads - Zhang, X.; Hao, Hong; Wang, Z. (Pergamon, 2014)
A series of field blasting tests of glass windows to blast loadings have been recently conducted. This is the second paper to report the testing data on monolithic tempered glass windows. While the first paper reports the glass panel response and failure modes, the current paper concentrates on the glass fragments induced by the blast loadings. Thermally tempered glass has been often adopted for monolithic windows to reduce ejecting fragment hazards after window fracture. However, previous blast tests conducted on monolithic tempered glass reported that in addition to small cubic fragments the shattered glass panes could break into large and jagged fragments similar to the cases in annealed glass which poses much more debris threats than expected. A thorough study on tempered glass fragments produced by air blast pressure is therefore necessary for better protection of human safety. In this paper, fragment characteristics of monolithic tempered glass windows observed in blasting tests are analyzed and presented. 1.5 m X 1.2 m monolithic panes of two commonly used thicknesses, i.e. 6 mm and 10 mm, fully clamped onto the opening of an enclosed RC frame were tested with 5–10 kg TNT charge detonated at 4.5–12.3 m stand-off distances. Glass fragment mass and splash distributions both in front of and behind the windows were evaluated with respect to reflected pressure and glass specification. Fragment size and shape were also analyzed. High-speed cameras were used to monitor glass window fracture processes. Fragment velocities were determined by post-processing the high-speed camera images. Fragment ejecting velocities were evaluated with respect to the reflected impulse. Negative pressure was found to significantly influence the fragment ejecting velocity and fragment splash distributions.